PENYULUHAN KELAS IBU HAMIL TENTANG P4K - Puspita, Yenni (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Birth Planning and Complication Prevention (P4K) Program with Stickers isan breakthrough effort in accelerating the decline in the death rate of mother andnewborn baby. The Activity build on potential of the community, to preparation andsave the mothers and newborn baby. Based on preliminary survey at clinic prumnas doresearcher interview not structur to 8 pregnant women including two pregent womenwho have been putting up stickers P4K and 6 pregnant women have not planned andhave not stick to P4K Stiker at home. Objective to know how the class counselingpregnant woment to knowledge and participation of expectant mother with theinstallation of the program on a p4k sticker. This type of research is Experimental designpre one group pretest-posttest . Samples taken by total sampling. The Data analysis doin univariat and bivariat wWilcon test at α 5%. Research Result: that that the avererageKnowledge before to the counseling and after the counseling is There is difference ofknowledge And participation of P4K sticker installation before and after the counselingin rejang lebong prumnas Bengkulu health center (p value = 0,000).